Indonesian Representation in Social Media (Semiotic Analysis of Roland Barthes in @instanusantara Instagram Account) - Keke Meidyluana Sitalaksmi; Dr. Lintang Ratri Rahmiaji, M.Si (Interaksi Online, 2016)
Instanusantara is one of the social media account in instagram that present natural beauty and culture photo of Indonesia. All of photos in @instanusantara entirely taken in Indonesia and is a natural and cultural beauty photo. The aim of this research is to know the Indonesian representation based on Semiotic analysis and to dismantle the myth of what was built by instanusantara. In analyzing this Instanusantara instagram account using semiotic researchers from Roland Barthes, which in the theory is stated that there are two systems sign denotation and connotation. The results of this study showed that the denotation of the 12 pictures are analyzed mentioning that Indonesia's tourism is travel related to nature, a photograph of the beach or mountains, is dominated by color photo of green or blue, is a landscape photo, instanusantara’s logo in every picture and there is a description that explains the photo. Connotations of 12 and shows that travel in Indonesia is not only Bali, Indonesia is an archipelagic country, Indonesia's tourism is nature, landscape photographs used to take pictures as scenery objects, logos instanusantara used to indicate the identity of Indonesia. Based on these results, it can be concluded that Indonesia is represented as an beautiful archipelago / Nusantara, Indonesian tourism is a tour that presents the natural beauty of the culture, and Indonesia is not only synonymous with Bali as what people know so far.